Rancang Bangun Aplikasi Analisis Pengaruh KualitasPelayanan terhadap Kepuasan Pasien Rawat Inap pada GRIU Graha Amerta Surabaya - Santi, Lintang Sekar; Sulistiowati, Sulistiowati; Maulana, Yoppy Mirza (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
The need for health every year have increased, it make hospitals have a competition to improved their services. As same asGRIU Graha Amerta Surabaya, as governments hospitals, it’s trying to gave the best service to compete with others. So that the patient satisfaction becomes main focus. To improve patient satisfaction on the service quality, the measurement of quality of services needs to be done. To measuring the service quality purposed to get information about the influence of service quality factors. The information will be used to descission support management. To support the purpose of GRIU Graha Amerta Surabaya, proposed an application to analysis influence of the service quality on inpatients satisfaction. It will be applied multi linier regression method to calculate and produce information the factors that influence and not influence on the inpatients satisfactions.